If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 50 = -9p + -4 Reorder the terms: 50 = -4 + -9p Solving 50 = -4 + -9p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '9p' to each side of the equation. 50 + 9p = -4 + -9p + 9p Combine like terms: -9p + 9p = 0 50 + 9p = -4 + 0 50 + 9p = -4 Add '-50' to each side of the equation. 50 + -50 + 9p = -4 + -50 Combine like terms: 50 + -50 = 0 0 + 9p = -4 + -50 9p = -4 + -50 Combine like terms: -4 + -50 = -54 9p = -54 Divide each side by '9'. p = -6 Simplifying p = -6
| 2(x+3)+4x=36 | | 31h=6136 | | 4x+3-6x=9 | | 33*64=n | | 6-(n-4)=18 | | 2112/64= | | -16=8x-24 | | 2.9h-5.1=4.7 | | 4x^2+20x-23=0 | | 16=4k+m | | 8x-48=180 | | X=2.5(7.6)+7 | | -8y-5y=12-9y | | 3-4x=35 | | 8h=15830 | | 5x-1/2(3x+8)=-4+3x | | -x-4y=-12 | | 9x^2-30x+23=0 | | 8(2m+1)= | | -9-8=10x+10-9x | | x+0.25=-1.25 | | 3(-2.5y+7)=-36 | | -2(4-x)-7=15 | | 12(p+5)=13p+2 | | 44=5x-3x | | 3(y-5)=-3y | | 8x-5-2x+5=x-18+8x | | 2x+15=95 | | 22+3x=-4(5-6x) | | 32=4 | | 10p-45=3(p-15) | | -3(a+5)+9=15 |